2015
DOI: 10.1139/cjes-2014-0108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and dispersal of indicator minerals associated with the Pine Point Mississippi Valley-type (MVT) district, Northwest Territories, Canada

Abstract: A glacial dispersal study was conducted around a subcropping Pb-Zn deposit (O28) in the Pine Point Mississippi Valley-type (MVT) district, Northwest Territories, Canada, with the intent of characterizing and documenting the indicator minerals and their dispersal from a known orebody. Mapping of striations adjacent to deposit O28, and throughout the Pine Point district, along with observed glacial stratigraphy, indicate that there are three phases of ice flow that have affected the Pine Point district. Sphaleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Four ice-flow phases were identified through till macrofabric analysis that correlates well with the erosional record around the Pine Point mining district (Table 4; Oviatt and Paulen 2013;Oviatt et al 2015). This confirms the glacial history of the Pine Point region is much more complex than previously reported (Lemmen et al 1994).…”
Section: Unit Separation and Ice Flow Chronologysupporting
confidence: 79%
See 1 more Smart Citation
“…Four ice-flow phases were identified through till macrofabric analysis that correlates well with the erosional record around the Pine Point mining district (Table 4; Oviatt and Paulen 2013;Oviatt et al 2015). This confirms the glacial history of the Pine Point region is much more complex than previously reported (Lemmen et al 1994).…”
Section: Unit Separation and Ice Flow Chronologysupporting
confidence: 79%
“…Subsequent work, using visual observations, grain size, till-matrix geochemistry, indicator mineral abundance, and pebble lithologies, identified four distinct till units at open-pit K-62 (Rice et al 2013). Oviatt and Paulen (2013) and Oviatt et al (2015) mapped striae exposed on the bedrock shoulders of the open-pits and identified three main ice flow phases which correlated with the regional ice flow pattern established from the geomorphological record in the area (Rice et al 2013). These investigations identified the earliest flow phase was to the southwest (ϳ230°), followed by a dominant flow phase to the northwest (ϳ300°), and finally, a west-southwestward flow phase associated with ice streaming during deglaciation (ϳ250°) (Fig.…”
Section: Location Quaternary Geology and Previous Workmentioning
confidence: 99%
“…Fieldwork conducted by the Geological Survey of Canada in 2010 documented cross‐striated bedrock surfaces on the shoulders (i.e. bedrock benches) of several exposed open pits (McClenaghan, Paulen, & Oviatt, ; Oviatt, ; Oviatt et al, ; Oviatt, Paulen, McClenaghan, Gleeson, & Paradis, ). Striation measurements and cross‐cutting relationships (Figure ), combined with aerial‐photograph and satellite‐imagery landform analyses, have determined a minimum of three ice‐flow trajectories (McClenaghan et al, ; Oviatt et al, ).…”
Section: Glacial Geologymentioning
confidence: 99%
“…bedrock benches) of several exposed open pits (McClenaghan, Paulen, & Oviatt, ; Oviatt, ; Oviatt et al, ; Oviatt, Paulen, McClenaghan, Gleeson, & Paradis, ). Striation measurements and cross‐cutting relationships (Figure ), combined with aerial‐photograph and satellite‐imagery landform analyses, have determined a minimum of three ice‐flow trajectories (McClenaghan et al, ; Oviatt et al, ). The earliest flow phase was to the south‐west (~230°), a subsequent significant flow phase to the northwest (~300°) and a final west south‐westward (~250°) deglacial flow were identified in several pits, including O‐28.…”
Section: Glacial Geologymentioning
confidence: 99%
See 1 more Smart Citation